Assessment of water conflict in Mae Chaem River Basin, Northern Thailand - Ekkawatpanit, C.; Kazama, S.; Sawamoto, M.; Sarukkalige, Priyantha Ranjan (Routledge, Taylor & Francis Group, 2009)
For this study, we conducted a quantitative water resources assessment of the Mae Chaem River Basin, Thailand, an area with dry season water scarcity and water use conflicts between upstream and downstream inhabitants. The block-wise TOPMODEL with the Muskingum–Cunge flow routing method (BTOPMC) was used to predict run-off in 21 sub-basins and Geographic Information System (GIS) was employed to collect information for crop water demand evaluation. Four sub-basins exhibited critical water conditions in 2000. The conversion of forestlands into agricultural lands during the past decade has engendered water scarcity in the dry season and flooding in the wet season.